The Effectiveness of Using a Crossword Game on Quizizz in Teaching Vocabulary - Ririn Andini; Eusabinus Bunau; Eka Fajar Rahmani (Universitas Pahlawan Tuanku Tambusai, 2026)
Vocabulary acquisition is a fundamental component of English language learning, yet students often struggle to retain newly learned words when taught through conventional instructional methods. Although various digital technologies have been integrated into vocabulary instruction, limited research has examined the effectiveness of combining traditional crossword puzzles with the Quizizz platform to create an engaging mobile-assisted learning experience. This study aimed to investigate the effectiveness of using Quizizz-based crossword games in improving students’ English vocabulary mastery. A pre-experimental quantitative design with cluster random sampling was employed to measure students’ vocabulary achievement before and after the treatment. The findings indicate that students’ post-test performance exceeded their pre-test performance, with mean scores increasing from 92.81 to 98.55 after participating in Quizizz-based crossword activities. Statistical analysis further demonstrated a significant improvement in vocabulary achievement following the intervention, indicating that the treatment positively influenced students’ learning outcomes. These findings suggest that integrating crossword games into the Quizizz platform provides an interactive and motivating learning environment that enhances vocabulary acquisition. Therefore, Quizizz-based crossword games can be considered an effective digital instructional strategy for supporting English vocabulary learning in classroom contexts.